If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -2) + x(3x + -4) = (5x + 6)(x + -4) Reorder the terms: x(-2 + 2x) + x(3x + -4) = (5x + 6)(x + -4) (-2 * x + 2x * x) + x(3x + -4) = (5x + 6)(x + -4) (-2x + 2x2) + x(3x + -4) = (5x + 6)(x + -4) Reorder the terms: -2x + 2x2 + x(-4 + 3x) = (5x + 6)(x + -4) -2x + 2x2 + (-4 * x + 3x * x) = (5x + 6)(x + -4) -2x + 2x2 + (-4x + 3x2) = (5x + 6)(x + -4) Reorder the terms: -2x + -4x + 2x2 + 3x2 = (5x + 6)(x + -4) Combine like terms: -2x + -4x = -6x -6x + 2x2 + 3x2 = (5x + 6)(x + -4) Combine like terms: 2x2 + 3x2 = 5x2 -6x + 5x2 = (5x + 6)(x + -4) Reorder the terms: -6x + 5x2 = (6 + 5x)(x + -4) Reorder the terms: -6x + 5x2 = (6 + 5x)(-4 + x) Multiply (6 + 5x) * (-4 + x) -6x + 5x2 = (6(-4 + x) + 5x * (-4 + x)) -6x + 5x2 = ((-4 * 6 + x * 6) + 5x * (-4 + x)) -6x + 5x2 = ((-24 + 6x) + 5x * (-4 + x)) -6x + 5x2 = (-24 + 6x + (-4 * 5x + x * 5x)) -6x + 5x2 = (-24 + 6x + (-20x + 5x2)) Combine like terms: 6x + -20x = -14x -6x + 5x2 = (-24 + -14x + 5x2) Add '-5x2' to each side of the equation. -6x + 5x2 + -5x2 = -24 + -14x + 5x2 + -5x2 Combine like terms: 5x2 + -5x2 = 0 -6x + 0 = -24 + -14x + 5x2 + -5x2 -6x = -24 + -14x + 5x2 + -5x2 Combine like terms: 5x2 + -5x2 = 0 -6x = -24 + -14x + 0 -6x = -24 + -14x Solving -6x = -24 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. -6x + 14x = -24 + -14x + 14x Combine like terms: -6x + 14x = 8x 8x = -24 + -14x + 14x Combine like terms: -14x + 14x = 0 8x = -24 + 0 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| -126=14*k | | 6z+5(z-6)= | | (5e-6)-4=-3 | | 4x-1-4x+7= | | 4x+x=-27 | | 21=-7*n | | -13=-8b-5b | | -6x-50+12x=64 | | 4x-4=27 | | 0.15x+0.6(x-2)=0.01(3x-5) | | 5(-5)-2(2)= | | 11t/28-t/4=1 | | x-2(3x-2)=-6+4x-8 | | -15*x=2 | | g(-x)=x^2+10x+35 | | 5-4(3m-6)=5 | | 4(3+1.25)+5y=12.00 | | 6y+3-8=-37 | | 5x+6x-(3x+5)= | | V+9=1 | | x^3-6x+9x=0 | | 6n+4+2=-24 | | -10-5(1+j)= | | -2x+1=-2(x+5) | | 6x-8+8=6 | | 3(-9h+10)= | | 13/1/3 | | 3(x^2-1)=24 | | 5(-7g-2)= | | 5/2(n-92) | | x/7-x/5=1/7 | | -68+5x+x=64 |